2024
DOI: 10.3390/life14020179
|View full text |Cite
|
Sign up to set email alerts
|

The Contemporary Role of Speckle Tracking Echocardiography in Cirrhotic Cardiomyopathy

Yannis Dimitroglou,
Constantina Aggeli,
Alexandra Alexopoulou
et al.

Abstract: Cirrhotic cardiomyopathy (CCM) is characterized by elevated cardiac output at rest, an inability to further increase contractility under stress, and diastolic dysfunction. The diagnosis of CCM is crucial as it can lead to complications during liver transplantation. However, its recognition poses challenges with conventional echocardiography techniques. Speckle tracking echocardiography (STE), particularly global longitudinal strain (GLS), is a novel index that enhances the diagnostic efficacy of echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Further studies have also investigated the relationship between GLS and the severity of cirrhosis according to the model for end-stage liver disease (MELD) and the Child-Pugh scores, and whether GLS is related to prognosis [ 62 ]. Mechelink et al showed that patients with advanced cirrhosis, including significant portal hypertension or decompensated cirrhosis, had a higher resting GLS.…”
Section: Diagnosismentioning
confidence: 99%
See 4 more Smart Citations
“…Further studies have also investigated the relationship between GLS and the severity of cirrhosis according to the model for end-stage liver disease (MELD) and the Child-Pugh scores, and whether GLS is related to prognosis [ 62 ]. Mechelink et al showed that patients with advanced cirrhosis, including significant portal hypertension or decompensated cirrhosis, had a higher resting GLS.…”
Section: Diagnosismentioning
confidence: 99%
“…Mechelink et al showed that patients with advanced cirrhosis, including significant portal hypertension or decompensated cirrhosis, had a higher resting GLS. However, other studies report contradictory findings: for instance, more advanced cirrhosis, as defined by Child-Pugh or MELD, was not necessarily associated with a significantly higher GLS [ 62 ]. In the study by Mechelink et al , patients with a higher GLS were characterized by a lower contractile reserve, as shown by a dobutamine stress test, than patients with an initially lower GLS.…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations